2015
DOI: 10.1002/ppsc.201500059
|View full text |Cite
|
Sign up to set email alerts
|

CuNPs for Efficient Photocatalytic Hydrogen Evolution

Abstract: A simple and convenient way to syn­thesize CuNPs in situ for photocatalytic hydrogen evolution is reported. The average rate of hydrogen evolution is 35 mmol g–1 h–1, and it can be recycled for further use with persistent photocatalytic efficiency in a stable and easy‐to‐­operate system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…It is estimated that only a few hundred tons of the total production were converted to Cu-based nanoparticles (Cu NPs) , despite there being many emerging applications for nano-Cu materials. Many applications involve the traditional role of Cu as a conductor, such as conductive dyes (Albrecht et al, 2016;Hokita et al, 2015;Tam and Ng, 2015;Kharisov and Kharissova, 2010;Tsai et al, 2015;Gopalan et al, 2016) or heat transfer fluids (Park et al, 2015;Montes et al, 2015;Azizi et al, 2016;Rizwan-ul-Haq et al, 2016), but the use of nano-Cu is rapidly expanding into novel applications such as catalysts in organic synthesis (Dugal and Mascarenhas, 2015;Lennox et al, 2016;Barot et al, 2016), sensors (Albrecht et al, 2016;Tsai et al, 2015;Gopalan et al, 2016;Brahman et al, 2016;Pourbeyram and Mehdizadeh, 2016), solar cells (Yoon et al, 2010;Parveen et al, 2016;Shen et al, 2016), light-emitting diodes , hydrogen generation (Liu et al, 2015a;Liu et al, 2015b), and drug delivery (Woźniak-Budych et al, 2016). Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles …”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that only a few hundred tons of the total production were converted to Cu-based nanoparticles (Cu NPs) , despite there being many emerging applications for nano-Cu materials. Many applications involve the traditional role of Cu as a conductor, such as conductive dyes (Albrecht et al, 2016;Hokita et al, 2015;Tam and Ng, 2015;Kharisov and Kharissova, 2010;Tsai et al, 2015;Gopalan et al, 2016) or heat transfer fluids (Park et al, 2015;Montes et al, 2015;Azizi et al, 2016;Rizwan-ul-Haq et al, 2016), but the use of nano-Cu is rapidly expanding into novel applications such as catalysts in organic synthesis (Dugal and Mascarenhas, 2015;Lennox et al, 2016;Barot et al, 2016), sensors (Albrecht et al, 2016;Tsai et al, 2015;Gopalan et al, 2016;Brahman et al, 2016;Pourbeyram and Mehdizadeh, 2016), solar cells (Yoon et al, 2010;Parveen et al, 2016;Shen et al, 2016), light-emitting diodes , hydrogen generation (Liu et al, 2015a;Liu et al, 2015b), and drug delivery (Woźniak-Budych et al, 2016). Based on the antifungal and antimicrobial properties of Cu + 2 , Cu NPs are actively being developed for applications in agriculture and food preservation (Park et al, 2015;Montes et al, 2015;Dugal and Mascarenhas, 2015;Ray et al, 2015;Kalatehjari et al, 2015;Ponmurugan et al, 2016;Maniprasad et al, 2015;Majumder and Neogi, 2016;Villanueva et al, 2016), textiles …”
Section: Introductionmentioning
confidence: 99%
“…For Cu/FTO samples, the diffraction peaks at 43.3 • , 50.5 • , and 74.1 • are assigned to the (111), (200), and (220) planes of face-centered cubic Cu (JCPDS No. 04-0836) [26]. As the content of Cu increases, the intensity of characteristic peaks becomes stronger.…”
Section: Introductionmentioning
confidence: 97%
“…Here, based on our previous research [15,22,25,26], we reported that FTO nanopowders were fabricated by a typical sol-gel method and then modified with Cu further by a facile hydrothermal method. The Cu/FTO nanocomposites were characterized by X-ray diffraction (XRD), UV-VIS, energy dispersive X-ray (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[28,31] A Xe lamp (300 W, PLS-SXE300CUV, Perfect Light Co. Ltd., Beijing) was applied as the light source. In a typical photocatalytic H 2 production experiment, Cu/FTO was immersed in an aqueous solution (70 mL) containing 60 mL of water and 10 mL of lactic acid as an electron sacrificial agent (pH=6.40).…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…However, noble metal silver is rare and expensive, which hinders its large-scale application. [27] In another attempt we used Cu nanoparticles [28] which are cheap and plasmonic as photocatalyst, [29] also exhibiting excellent photocatalytic activity. And yet Cu nanoparticles macroscopically tend to aggregate easily during preparation, so that the photocatalytic activity may be severely impaired by the large diameter and self-aggregation of the synthesized Cu NPs.…”
Section: Introductionmentioning
confidence: 99%